2014
DOI: 10.1186/1472-6882-14-177
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian green propolis modulates inflammation, angiogenesis and fibrogenesis in intraperitoneal implant in mice

Abstract: BackgroundChronic inflammatory processes in the peritoneal cavity develop as a result of ischemia, foreign body reaction, and trauma. Brazilian green propolis, a beeswax product, has been shown to exhibit multiple actions on inflammation and tissue repair. Our aim was to investigate the effects of this natural product on the inflammatory, angiogenic, and fibrogenic components of the peritoneal fibroproliferative tissue induced by a synthetic matrix.MethodsChronic inflammation was induced by placing polyether-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 28 publications
1
19
0
1
Order By: Relevance
“…Total soluble collagen was measured in whole sponge homogenates by the Sirius Red reagent based-assay (Lima et al, 2014). Sponge discs from 4 animals per group were homogenized in 1 mL of PBS and 50 μL of the sample mixed with 50 μL of Sirius Red reagent.…”
Section: Quantification Of Collagen Content In Sponge Discsmentioning
confidence: 99%
“…Total soluble collagen was measured in whole sponge homogenates by the Sirius Red reagent based-assay (Lima et al, 2014). Sponge discs from 4 animals per group were homogenized in 1 mL of PBS and 50 μL of the sample mixed with 50 μL of Sirius Red reagent.…”
Section: Quantification Of Collagen Content In Sponge Discsmentioning
confidence: 99%
“…Studies have indicated that propolis is toxic when administered over a concentration of 2000 mg / kg [16]. In a study on rats, propolis administered via oral gavage at 500 mg / kg / day following intraperitoneal implant placement was found to have mitigating effects on inflammation, angiogenesis and fibrogenesis [27]. In a study conducted by Bereket et al, effect of propolis on the consolidation phase was investigated after distraction osteogenesis was performed on rabbits and the applications at oral doses of 100 mg / kg / day and 200 mg / kg / day were compared.…”
Section: Discussionmentioning
confidence: 99%
“…However, in rats LD50 was found to be 2-7.34 g / kg. The recommended daily dose is 1.4 mg / kg [26,27]. Studies have indicated that propolis is toxic when administered over a concentration of 2000 mg / kg [16].…”
Section: Discussionmentioning
confidence: 99%
“…Propolis significantly enhanced the production of collagen via the TGF-β1/Smad 2,3 signaling axis in wounded tissues [129]. Brazilian green propolis (from Baccharis dracunculifolia) can suppress an important inflammatory component (cell influx) and reduces the vascular permeability, angiogenesis without compromising the repair process by reducing fibrosis and increasing the pro-inflammatory markers and cytokine (TNF-α) involved in fibrinolytic activity [125,130]. Moreover, propolis has been used in combination with honey in a synergistic effect for wound healing [131], maybe due to the honey's hydrogen peroxide, high osmolality, acidity, nonperoxide factors, nitric oxide, and phenols [132].…”
Section: Propolismentioning
confidence: 99%